EFFECT OF SPRAYING AMINO ACIDS ON GROWTH AND YIELD OF BITTER GOURD PLANT GENOTYPES Momordica charantia L. AND ITS CHARANTIN CONTENT - & Al-jebory, Al-asadi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This Experiment was carried out in the plastic houses , College of Agricultural Engineering Sciences , University of Baghdad during the spring season 2018. Six inbred lines of bitter gourd were crossed full diallel crosses and planted during season 2018-2019 (six inbred lines +15 diallel hybrid + 15 Reciprocal hybrid + control hybrid). These genotypes were studied under the influence of amino acid spraying. This experiment was carried out using the split-plot design included two factors: The first factor represents amino acid spraying with control treatment and spraying phenylalanine amino acid at a concentration of 50 mg/L, and spraying Tyrosine amino acid at 100 mg/L with three times during the growing season. Represents the main plot were distributed randomly on three replicates.The second factor represents 37 genotypes of the bitter gourd represents Subplot. The results were showed highest that the interaction [T (5 × 4)] had total chlorophyll concentration in leaves (29.11 mg .g-1) , percentage of fruit setting (86.95%), fruit weight (122.6 g). While the interaction P (2×3) had the highest charnitin yield in the plant (0.857 g). The hybrid(2×3)  gave the highest charantine in the plant (0.760 g).